(untitled) (Journal of Environmental Science and Natural Resources, 2012)
Environmental Management Measure (EMM) model will be a well-designed approach for sustainable and effective solid waste management in Dhaka city. Environmental Management Measure (EMM) model has three instruments such as economic, regulatory and suasive which proposed in this paper. This paper discusses the situation of solid waste in Dhaka city as well as it offers environmental policy recommendations to concerned authorities including effective instruments to minimize the polluting behavior of individuals and industries and to recover the cost of pollution in the city. To improve solid waste management in Dhaka city, a combination of economic, regulatory and suasive instrument are recommended. The findings of the study will be helpful for policy maker, planner, implementer and other stakeholders towards adopting more effective strategy for management of solid waste in Dhaka city. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11601 J. Environ. Sci. & Natural Resources, 5(1): 99 - 111, 2012